Advances in dynamic compaction - Hamidi, Babak; Nikraz, Hamid; Varaksin, S. (Indian Geotechnical Society, 2011)
Dynamic Compaction is a ground improvement technique that was invented more than 40 years ago with the objective of improving the strength and reducing the compressibility of thick soil layers. In this technique a heavy pounder is dropped from a significant height a number of times onto a grid pattern. Research indicates that depth of improvement is a function of the square root of the impact energy; i.e. the pounder weight and pounder drop height. In the early days of dynamic compaction heavy duty cranes’ efficient lift capacities were limited to about 150 kN; however it soon became possible to lift heavier pounders using specially designed and manufactured rigs or tripods. The introduction of commercially available special cranes equipped with appropriate lift capacity now allows the use of pounders weighing up to 250 kN. More recently an innovative and patented pounder release mechanism called MARS has been developed. This system is capable of dropping pounders weighing up to 35 tons in free fall and automatically reconnecting to the pounder. This technology has resolved many practical problems and is able to transfer energy to the ground more efficiently. MARS was first successfully used for the treatment of 1.13 million m2 of loose desert dune sands with up to 28 m of thickness, and since then has also been used for treating saturated reclaimed sand and pre-collapsing karstic formations.